Targeting the Stromal Pro-Tumoral Hyaluronan-CD44 Pathway in Pancreatic Cancer - Koltai, Tomas (Int J Mol Sci, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest malignancies. Present-day treatments have not shown real improvements in reducing the high mortality rate and the short survival of the disease. The average survival is less than 5% after 5 years. New innovative treatments are necessary to curtail the situation. The very dense pancreatic cancer stroma is a barrier that impedes the access of chemotherapeutic drugs and at the same time establishes a pro-proliferative symbiosis with the tumor, thus targeting the stroma has been suggested by many authors. No ideal drug or drug combination for this targeting has been found as yet. With this goal in mind, here we have explored a different complementary treatment based on abundant previous publications on repurposed drugs. The cell surface protein CD44 is the main receptor for hyaluronan binding. Many malignant tumors show over-expression/over-activity of both. This is particularly significant in pancreatic cancer. The independent inhibition of hyaluronan-producing cells, hyaluronan synthesis, and/or CD44 expression, has been found to decrease the tumor cell’s proliferation, motility, invasion, and metastatic abilities. Targeting the hyaluronan-CD44 pathway seems to have been bypassed by conventional mainstream oncological practice. There are existing drugs that decrease the activity/expression of hyaluronan and CD44: 4-methylumbelliferone and bromelain respectively. Some drugs inhibit hyaluronan-producing cells such as pirfenidone. The association of these three drugs has never been tested either in the laboratory or in the clinical setting. We present a hypothesis, sustained by hard experimental evidence, suggesting that the simultaneous use of these nontoxic drugs can achieve synergistic or added effects in reducing invasion and metastatic potential, in PDAC. A non-toxic, low-cost scheme for inhibiting this pathway may offer an additional weapon for treating pancreatic cancer.